Immunobiology of the IL-15/IL-15Rα complex as an antitumor and antiviral agent. (December 2017) - Guo, Yin; Luan, Liming; Patil, Naeem K.; Sherwood, Edward R.
Graphical abstract: Highlights: IL-15 potently activates natural killer, NKT and memory CD8 + T cells and is crucial for their normal growth and differentiation. The half-life of IL-15 superagonist is significantly prolonged and the biological activity potently enhanced compared to native IL-15. The novel creation of IL-15 superagonist advances the potential of IL-15-based tumor and anti-viral immunotherapy. Preclinical studies show the advantage of IL-15 superagonist over native IL-15 in the treatment of multiple types of cancer. Recombinant IL-15 superagonist fusion proteins and engineered cells co-expressing IL-15/IL-15Rα complex provide novel immunotherapeutics. Abstract: Interleukin (IL)-15 is essential for natural killer (NK), NKT and memory (m) CD8 + T cell development and function, and is currently under investigation as an immunotherapeutic agent for the treatment of cancer. Recently, the creation of IL-15 superagonist by complexing IL-15 and its high affinity receptor alpha (IL-15 Rα) in solution, inspired by the natural trans -presentation of IL-15, advances the potential of IL-15-based tumor immunotherapy. IL-15 superagonist shows promising advantages over monomeric IL-15 such as sustaining high circulating concentrations due to prolonged half-life and more potently stimulating NK and CD8 + T effector lymphocytes. So far, there are three different forms of recombinant IL-15 superagonist fusion protein based on configurational modifications. Gene therapy using engineered cells co-expressing IL-15/IL-15 Rα complex for cancer treatment is also emerging. All forms have demonstrated efficacy in causing tumor regression in animal studies, which provides strong rationale for advancing IL-15 superagonist through clinical trials. To date, there are fourteen phase I/II IL-15 superagonist trials in cancer patients and one phase I trial in HIV patients. Information generated by ongoing trials regarding the toxicity and efficacy of IL-15 superagonist is awaited. Finally, we elaborate on immunotoxicity caused by IL-15 superagonist in preclinical studies and discuss important safety considerations.